The Effect of Eye Exercise on Eye Fatigue on Computer Users - Nurul Kartika Sari; Yehud Maryen; Indah Oktavia (Institute of Computer Science (IOCS), 2022)
Background: Eye fatigue is a complaint often found in computer users' efforts to overcome eye fatigue are eye exercises. This study aimed to determine the effect of eye exercises on computer users' eye fatigue at the National Land Agency of Sorong Regency office. Research methods: This study uses the Quasi-Experiment method, one group pre-test-post-test design. The sample used 23 respondents. The research instrument used is the observation sheet before and after the intervention. result: This study used the Wilcoxon test and obtained p value = 0.000 (p 0.05), where the average value of eye fatigue complaints before eye exercises were carried out was 12.00, while after the intervention, there was a decrease in the value of 0.00. Conclusions: Based on the study's results, it is known that eye exercises can reduce eye fatigue of computer users at the National Land Agency of Sorong Regency Office, so they can be used to prevent eye fatigue